The aesthetic of structural relationships in linear formations (Al-Academy, 2023)
This research is concerned with the study of (the aesthetic of constructive relations in linear composition) with what distinguished Arabic calligraphy through the style and artistic method in its construction, and the specifications it carries that enabled it to pay attention to building formations to achieve in its total linear ranges aesthetic values and relationships. Through the research, the models and the exploratory study that he obtained, the researcher was able to raise the research problem in the first chapter according to the following question: What is the aesthetic of constructive relations in linear formation?The importance of the research in achieving the aesthetics of the formations, which is a wide field according to the transformation of the structural form, was marked by the search’s disclosure of the aesthetics of the structural relationship in the linear composition written by calligraphers in (Iraq and Turkey) for the period from (1419-1998), (1430-2008) The second chapter included two topics, the first is beauty in Arabic calligraphy, and the second is the aesthetics of constructive relations, and the third chapter includes research procedures based on the descriptive analytical approach. Intentionality was analyzed according to the research tool represented by the research form, which included four pillars whose validity was supervised by a group of specialists.